Pengaruh Ukuran Kawat dan Jarak Alur Stator Terhadap Nilai Arus Starting Motor Induksi 3 Fasa - Hendrick, Fran; Liliana, Liliana (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2024)
The use of electric motors in industry often experiences damage caused by several things, including high starting current surges, overload or full load, loss of one phase in the electric motor, and other causes of damage to the 3-phase motor. The main problem that occurred in this research was damage caused by high starting currents, where in the case study many 3-phase motors were used to drive factory machines. The use of 3-phase motors to drive factory machines is often damaged by unstable currents in the machines. This is because the time and workers for monitoring are very minimal and the materials for repairing machines are inadequate. In this way, the solution for repairing a 3-phase motor is to replace and rewind the damaged motor so that it can be used again. This research aims to find a solution on how to reduce high starting currents in 3-phase motors by utilizing the influence of replacing damaged induction motor components as well as repair methods used in starting when rewinding 3-phase motors. The research results from the groove distance with a wire size of 0.90 mm showed that the groove distance of 9, 9, 8 was 29.3, and at a distance of 10, 10, 10 it had a current of 31 A with no-load testing and recommended groove distances of 10, 10, 10. Next, testing wire sizes of 0.75 mm and 0.90 mm with distances of 10, 10, 10, and 9, 9, 8 without load obtained 26.1 A and 27.4 A while 0.90 mm was 30, 7 A and 28, 1 A. The load was 43.5 A and 43.9 A, while 0.90 mm was 51.3 A and 49.3 A. From the test results, the largest current decrease was at a distance of 10, 10, 10 with a wire size of 0.75 mm. Keyword - 3 Phase Induction Motor, Groove Spacing, Starting, Wire Size.